PERTIMBANGAN HAKIM TERHADAP PERMOHONAN ISBAT NIKAH DARI PERNIKAHAN TIDAK TERCATAT DI PENGADILAN AGAMA PADANG KELAS IA (Studi Penetapan Hakim Nomor 1046/Pdt.G/2024/PA.Pdg) - Tuti Kelana Sembiring; Susanti Sembiring; Silvia Millenia Afrila (Ensiklopedia of Journal, 2026)
Abstract: The provisions regarding marriage registration are regulated under Article 2 of Law Number 1 of 1974 on Marriage, as amended by Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 on Marriage, which stipulates that a marriage is considered legally valid if it is officially registered. For marriages that have not been registered, the parties may submit an application for isbat nikah to the Religious Court in the jurisdiction where the marriage was conducted. This study aims to examine the judges’ considerations and the legal consequences arising from applications for isbat nikah involving unregistered marriages. This research is descriptive in nature, focusing on the depiction of applicable legal regulations in relation to the issues under study. The approach employed is a normative juridical approach. Based on the court determinations and subsequent analysis, the study draws the following conclusions. First, the judges assessed that the marriage between the applicant and her husband fulfilled all the requirements and pillars of an Islamic marriage in accordance with the Marriage Law and the Compilation of Islamic Law. Accordingly, the applicant’s petition for isbat nikah was granted. Second, as a legal consequence of granting the isbat nikah application, the applicant and her husband are declared legally married both religiously and under state law. The applicant is required to register the marriage with the Marriage Registrar at the Office of Religious Affairs where the marriage took place. Subsequently, the applicant is also obliged to obtain essential civil documents, including a marriage certificate, family card, and the child’s birth certificate.  Keywords: Judge, Isbat Nikah, Unregistered Marriage.